Pembelajaran Bunyi Bahasa Indonesia Menggunakan Metode Field Trip pada Siswa Muslim Suksa School, Thailand - Fahreza, Shinta Adelia; Syamsuyurnita, Syamsuyurnita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Field trip is a teaching and learning method through visiting a place and using Indonesian as a comparison of the meaning of Tagalog itself. The method used in this research is a qualitative descriptive method. According to Mukhtar (2013: 10), the qualitative descriptive research method is a method used by researchers to find knowledge or theory regarding research at a certain time. From the percentage of words prepared by the students spoken, the total number of words spoken was 14 words with the number of students tested being 5 people. Based on figure 1, it can be concluded that: [1] The student named Anurak got a percentage of 9% in the number of correct language sounds, [2] the student named Narong got a percentage of 28% in the correct number of language sounds, [3] the student named Songkarn managed to get a percentage of 27% in the correct number of language sounds, [4] the student named Malivalaya managed to get a percentage of 18%.